(untitled) (Journal of Philosophy Culture and Political Science, 2019)
The article examines the causes of the ethnic confl icts in Caucasus and analyses the common features and mistakes, which were committed at the initial stages of the armed confl ict. The author generalizes the common factors caused escalation of the confl ict, and at the same time distinguishes the peculiarities of the each case. The article is based on the theoretical conclusions of the foreign sources, published in English language.